1995
DOI: 10.1176/jnp.7.2.213
|View full text |Cite
|
Sign up to set email alerts
|

An automated electronic method for quantifying spinning (circling) in children with autistic disorder

Abstract: This pilot study examined and quantified rotational asymmetry (the tendency to turn preferentially to the right or left side). An automated device was used to measure turning (circling) in 9 children with autism and 27 normal control subjects and confirmed clinical observations of stereotypical spinning behavior in patients with autism. This behavior was significantly preferential toward the left side relative to control subjects (P = 0.0009, two-tailed). Group membership accounted for approximately 40% of var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Based on the work of Bracha et al [1], we had expected RAV to be linked with ratings of stereotyped behaviors in the ASD group. These authors reported that spinning in children with ASD had a left turn bias which they attributed to right sided neglect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the work of Bracha et al [1], we had expected RAV to be linked with ratings of stereotyped behaviors in the ASD group. These authors reported that spinning in children with ASD had a left turn bias which they attributed to right sided neglect.…”
Section: Discussionmentioning
confidence: 99%
“…Automated devices to detect stereotypic behaviors, for example, have been shown to be a promising alternative to rating scales, as this minimizes the role of human decision making and can provide much more quantitative and dynamic information [1,2]. Further, eye tracking devices have yielded important information relevant to both early detection [3] and toward understanding the nature of the social deficits in autism [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In triadic interactions involving an object, the fact that two partners perceive different affordances of the object may also lead to less smooth interactions. Preference for producing or observing spinning or rotating movements (spinning objects, watching washing machine rotating, spinning wheels of toy cars) is for instance common in children with ASD (Bracha et al, 1995). If one child is for instance continuously spinning the wheels of a toy car while the other child is “driving” the car, this will probably decrease the amount of social interaction between the children.…”
Section: Understanding Social Engagement In Autismmentioning
confidence: 99%
“…The last-mentioned author group reported that the left-ward turning preference of dance-naïve children shifted to a right-ward preference in professional young dance students (mean age = 11.9 ± 1.1years; N = 36). One more study investigated circling behavior (spinning around) in children with autism (Bracha, Livingston, Dykman, Edwards, & Adam, 1995) and found a significant left-ward bias, which was absent, however, in the control group of 27 healthy elementary school children (average age of 6 years). In the present study we aimed to further explore turning bias in a large sample of children, both girls and boys.…”
Section: Introductionmentioning
confidence: 99%